Britain in the Seventies – Our Unfinest Hour? - Kenneth O. Morgan (Revue Française de Civilisation Britannique)
In popular recollection, the 1970s have gone down as the dark ages, Britain’s gloomiest period since the second world war, set between Harold Wilson’s ‘swinging sixties’ and Margaret Thatcher’s divisive eighties. Forty years on, it is appropriate for the historian to examine how valid these depressing verdicts on the United Kingdom really were. Were the dark ages an exaggerated fabrication of excited journalists and ill-disposed foreigners? Or did the seventies uncover something fundamentally wrong about this ancient people which survives to diminish its authority and restrict its vision down to the present day?